Optimal bidding price strategy in electricity auction for new capacity in Malaysia considering uncertainty: article / Muhammad Syukur Amran - Amran, Muhammad Syukur (Universiti Teknologi MARA (UiTM), 2013)
The objective of this project is to find the optimal biding price in electricity auction for new power - plants in Malaysia. This strategy is applied to three most common generation technologies which is coal, gas-fired (CCGT), and nuclear. It is important for the generating company to determine the minimum bid prices that it should submit in the auction in order to ensure that the investment would be profitable and meet the Minimum Acceptable Rate of Return (MARR) aimed by the company. The uncertainty such as fuel cost, overnight cost, operation and maintenance (O&M) cost and utilization factor are considered in the model. The effect of these uncertainties on the bid prices is studied using 1) sensitivity analysis and 2) probabilistic analysis. Results show that the bid prices of nuclear is more sensitive to the changes in investment cost, O&M cost and utilization factor and less sensitive to the fuel cost than coal and CCGT. On the other hand the bid price of CCGT is more sensitive to the fuel cost. The sensitivity of coal plant shows result somewhere in between the nuclear and CCGT.